LACK OF FINANCING PUBLIC HEALTH AS A CAUSE OF LEGAL RESPONSIBILITY OF OBSTETRICIAN-GYNECOLOGISTS - Владимир Анатольевич Артымук (The Publishing House Medicine and Enlightenment, 2019)
Objective - to show the relationship of the lack of funding for regional health care and the legal responsibility of obstetrician-gynecologists. Materials and methods. The analysis of the regulatory framework for the provision of medical care and financing of the health care system in the Russian Federation. A review of modern scientific literature is presented, as well as own experience in the protection of obstetrician-gynecologists in the context of a shortage of regional health care funding. It is shown that despite the fact that health care is an integral part of the structure of the social sphere of social life, the primary goal of which is to preserve and strengthen the health of the population, in practice, the state in the framework of guaranteed programs proceeds only from minimal guarantees that are not identical to societally acceptable social needs . Conclusion. Currently, the lack of funding for health care in the regions of the Russian Federation is the cause of the occurrence of precedents of both civil and criminal liability of obstetrician-gynecologists, which is the object of a lawyer.